SELF-DISCLOSURE AS A HERMENEUTIC MODERATOR IN TELISIK’S GAMIFIED LEARNING TRAJECTORY - Lakilaki, Eogenie; Kusmeri, Kusmeri; Komariah, Imas; Budiman, Arief; Marwa, Annisa (Institut Pendidikan Tapanuli Selatan, 2026)
This study investigates the contribution of gamified learning and self-disclosure counselling within the TELISIK digital ecosystem in enhancing students’ readiness for higher education, proxied by UTBK scores. Using a quantitative design, data from 82 participants in South Sumatra were collected through structured questionnaires and analysed with regression modelling. The results demonstrate that gamified learning significantly improves academic performance by strengthening motivation, engagement, and persistence, while self-disclosure counselling also contributes positively by fostering reflection, psychological safety, and resilience. However, the interaction between the two was not statistically significant, indicating that gamification and counselling function effectively in parallel rather than synergistically. These findings provide theoretical support for constructivist learning, illustrating how behavioural stimulation and reflective practice independently enhance outcomes. They also align with SDGs 4 (Quality Education), emphasising TELISIK’s potential as a community-driven platform to expand access to higher education in disadvantaged regions. The study offers practical insights for policymakers and edtech developers in optimising digital ecosystems to strengthen academic readiness. Limitations include the modest sample size, reliance on UTBK scores as a single performance indicator, and the absence of formally trained counsellors in TELISIK. Future research should broaden samples, adopt longitudinal designs, and incorporate multidimensional learning outcomes to enrich theory and practice